The ideophones in Tshivenda : a syntactic and semantic analysis - Mundalamo, Rabelani Phyllis (My University, 2002)
Refer to the document
Thesis (M. A. (African Languages)) -- University of Limpopo, 2002
Keywords: Ideophones; Syntactic analysis; Semantic analysis; Tshivenda language; Tshivenda language; Grammar, comparative and general -- Ideophone